+0  
 
0
68
1
avatar

Express $\frac 1{1+\frac 1{1-\frac 1{1+i}}}$ in the form $a+bi$, where $a$ and $b$ are real numbers.

 

In case you have trouble reading that, here's a simpler version:

1/(1+1/(1-1/(1+i))).

Guest Sep 18, 2018
 #1
avatar
0

Simplify the following:
1/(1/(-1/(i + 1) + 1) + 1)

Multiply numerator and denominator of (-1)/(i + 1) by 1 - i:
1/(1/((-(-i + 1))/((i + 1) (-i + 1)) + 1) + 1)

(1 + i) (1 - i) = 1×1 + 1 (-i) + i×1 + i (-i) = 1 - i + i + 1 = 2:
1/(1/(1 - ((-i + 1))/2) + 1)

Put each term in 1 - (-i + 1)/2 over the common denominator 2: 1 - (-i + 1)/2 = 2/2 + (-1 + i)/2:
1/(1/(2/2 + (i - 1)/2) + 1)

2/2 + (i - 1)/2 = ((1 i - 1) + 2)/2:
1/(1/((2 - 1 + i)/2) + 1)

Multiply the numerator of 1/((2 - 1 + i)/2) by the reciprocal of the denominator. 1/((2 - 1 + i)/2) = (1×2)/(2 - 1 + i):
1/(2/(2 - 1 + i) + 1)

2 - 1 + i = (2 - 1) + i = 1 + i:
1/(2/(i + 1) + 1)

Multiply numerator and denominator of 2/(i + 1) by 1 - i:
1/((2 (-i + 1))/((i + 1) (-i + 1)) + 1)

(1 + i) (1 - i) = 1×1 + 1 (-i) + i×1 + i (-i) = 1 - i + i + 1 = 2:
1/((2 (-i + 1))/2 + 1)

(2 (-i + 1))/2 = 2/2×(-i + 1) = -i + 1:
1/(-i + 1 + 1)

1 + 1 - i = (1 + 1) - i = 2 - i:
1/(-i + 2)

Multiply numerator and denominator of 1/(-i + 2) by 2 + i:
(i + 2)/((-i + 2) (i + 2))

(2 - i) (2 + i) = 2×2 + 2 i - i×2 - i×i = 4 + 2 i - 2 i + 1 = 5:
(i + 2)/5 = 2/5 + i/5

Guest Sep 18, 2018

4 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.